APPLICATION OF THE MATHEMATICAL MODEL MODFLOW ON A KARSTIC AQUIFER: THE CASE OF VIOTIKOS KIFISOS BASIN - Παναγόπουλος, A.; Δρακοπούλου, E.; Περλέρος, V. (Bulletin of the Geological Society of Greece, 2004)
MODFLOW is a very well verified code of mathematical modeling for simulation of saturated groundwater flow in porous medium. Groundwater flow simulation in discontinuity media (i.e. media characterized by dominance of secondary and tertiary porosity as opposed to primary porosity), such as karstic aquifers, utilizing specialized models is problematic. Due to existing impedes the use of the conventional model MODFLOW was attempted for the simulation of the karstic system of the Viotikos Kifisos river aiming predominantly at assessing the potential, restrictions, particularities and conditions under which such a modelling code could be implemented, especially when relatively restricted volume of raw data is available. Compilation and calibration of the model suggest that MODFLOW may in general be implemented and can provide useful results. As in every mathematical model, knowledge of the assumptions made and the intrinsic restrictions involved is required, along with in-depth evaluation of its capabilities. The mathematical model of Viotikos Kifisos basin forms a valuable tool for management of its water resources and study of regional groundwater evolution.